Improving the assessment of predator functional responses by considering alternate prey and predator interactions. Issue 7 (12th June 2017) - Chan, K.; Boutin, S.; Hossie, T. J.; Krebs, C. J.; O'Donoghue, M.; Murray, D. L.
Abstract: To improve understanding of the complex and variable patterns of predator foraging behavior in natural systems, it is critical to determine how density‐dependent predation and predator hunting success are mediated by alternate prey or predator interference. Despite considerable theory and debate seeking to place predator–prey interactions in a more realistic context, few empirical studies have quantified the role of alternate prey or intraspecific interactions on predator–prey dynamics. We assessed functional responses of two similarly sized, sympatric carnivores, lynx ( Lynx canadensis ) and coyotes ( Canis latrans ), foraging on common primary (snowshoe hares; Lepus americanus ) and alternate (red squirrels; Tamiasciurus hudsonicus ) prey in a natural system. Lynx exhibited a hyperbolic prey‐dependent response to changes in hare density, which is characteristic of predators relying primarily on a single prey species. In contrast, the lynx–squirrel response was found to be linear ratio dependent, or inversely dependent on hare density. The coyote–hare and coyote–squirrel interactions also were linear and influenced by predator density. We explain these novel results by apparent use of spatial and temporal refuges by prey, and the likelihood that predators commonly experience interference and lack of satiation when foraging. Our study provides empirical support from a natural predator–prey system that (1) predation rate may not be limited at high prey densities when prey are small or rarely captured; (2) interference competition may influence the predator functional response; and (3) predator interference has a variable role across different prey types. Ultimately, distinct functional responses of predators to different prey types illustrates the complexity associated with predator–prey interactions in natural systems and highlights the need to investigate predator behavior and predation rate in relation to the broader ecological community.